Analysis of Village Fund Budget Management in Bololo Village, North Wasile District, East Halmahera Regency - Onesimus Siafu; Stanny Sicilia Rawung; Arie Frits Kawulur (International Journal of Applied Business and International Management, 2020)
Village Fund Allocation is a form of fulfilling villages’ right to carry out its autonomy in such a way that they grow and develop based on diversity, participation, original autonomy, democratization, community empowerment, and increasing the role of the village governments in providing services, improving welfare of the community and spurring development acceleration and growth of strategic areas. This study aims to analyze the management of the Village Fund Budget in Bololo Village, North Wasile District, East Halmahera Regency. This study made use the qualitative research in its methodology. The data sources were community leaders, and village heads, chosen to be key informants because they are considered to know extremely well and provide information about the things to be examined, to whom are asked which people will be the main informant. The snowball sampling was used for sampling. Based on the analysis results, it can be concluded that (1) the implementation of Village Fund Allocation (ADD) is uneven and not in accordance with Government Regulation Number 72 of 2005 and Village Law Number 6 of 2014. (2) The Government of Bololo Village, North Wasile District, East Halmahera Regency, in its accountability of Village Fund Allocation (ADD) is only one-sided and does not apply the transparency principle to the community.